Analisis Wacana Kritis Model Sara Mills terhadap Berita 3 Pria Sekap dan Perkosa Santriwati Magelang Berawal Kenal di Media Sosial - Herni Meilani; M. Surip; Syairal Fahmy Dalimunthe (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This research is qualitative research. This study aims to ensure that gender equality is not differentiated between men and women, because women also must get more attention. The data collection technique is done by analyzing online news. The Sara Mils model will be used as a reference for discourse analysis. The discourse analysis of the Sara Mills model will focus on the discourse of feminism, where a text will represent a woman. The Sara Mills method will examine two things, namely: first, who is the actor who will be positioned in the news and the interpreter of an event that occurs in the text. Second, how a reader will be positioned in the news text to see what the author wants the reader to do. There is injustice and bad judgment about a woman because women are often depicted and considered inferior to men in a text. The results of the study indicate that women are objects whose positions are often the subject of conversation for victims of sexual abuse, so they cannot present their own position. Through an analysis conducted on CNN Indonesia media, it shows that women who are victims of rape experience suffering, fraud and sexual violence that occurred during three days in a row.